War, institutions, and social change in the Middle East - Heydemann, Steven; Joint Committee on the Near and Middle East. (Berkeley : University of California Press, 2000)
Few areas of the world have been as profoundly shaped by war as the Middle East in the twentieth century. Despite the prominence of war-making in this region, there has been surprisingly little research investigating the effects of war as a social and political process in the Middle East. To fill this gap, War, Institutions, and Social Change in the Middle East brings together an international and interdisciplinary group of scholars who explore the role of war preparation and war-making on the formation and transformation of states and societies in the contemporary Middle East. Their findings pose significant challenges to widely accepted assumptions and present new theoretical starting points for the study of war and the state in the contemporary developing world. Heydemann's collaborators include political scientists, historians, anthropologists, and sociologists from the Middle East, Europe, and the United States. Their essays are both theoretically sophisticated and empirically rich, covering topics such as the effects of World War II on state-market relations in Syria and Egypt, the role of war in the rise of the Palestine Liberation Organization, the political economy of Lebanese militias, and the effects of the 1967 war on state and social institutions in Israel. The volume originated as a research planning project of the Joint Committee on the Near and Middle East of the Social Science Research Council.
War, institutions, and social change in the Middle East / Steven Heydeman -- Guns, gold and grain: war and food supply in the making of Transjordan / Tariq Tell -- The climax and crisis of the colonial welfare state in Syria and Lebanon during World War II / Elizabeth Thompson -- War, Keynesianism, and colonialism: explaining state-market relation in the postwar Middle East / Robert Vitalsim and Steven Heydemann -- Si vis stabilitatem, para bellum: state building, national security, and war preparation in Syria / Volker Perthes -- Changing boundaries and social crisis: Israel and the 1967 war / Joel S. Migdal -- War as leveler, war as midwife :Palestinian political institution, nationalism, and society since 1948 -- Yezid Sayigh -- War in the social memory of Egyptian peasants / Reem Saad -- War as a vehicle for the rise and demise of state-controlled society: the case of Ba'thist Iraq / Isam Al-Khafaji -- The political economy of civil war in Lebanon / Elizabeth Picard -- The cumulative impact of Middle Eastern Wars / Roger Owen.
"This volume is the result of a project on war and social change in the Middle East, directed and sponsored by the Social Science Research Council, Joint Committee on the Near and Middle East"--Title page verso
Includes bibliographical references (335-356) and index.
Print version record.
JSTOR
Keywords: Middle East -- History -- 20th century; War and society -- Middle East; War -- Economic aspects -- Middle East; Guerre et société -- Moyen-Orient.; Guerre -- Aspect économique -- Moyen-Orient.; Moyen-Orient -- Histoire -- 20e siècle.; HISTORY -- General; HISTORY -- Middle East -- General; War and society; War -- Economic aspects; Middle East; 1900-1999; History